DNA replication by a DNA-membrane complex extracted from Bacillus subtilis: site of initiation in vitro and initiation potential of subcomplexes. - Laffan, J (1987)
A DNA-membrane complex extracted from Bacillus subtilis was studied further as a model system for initiation of bacterial DNA replication in vitro. Of three subcomplexes purified from the crude complex by a combination of CsCl and sucrose gradient centrifugation, the synthetic capability of only one was inhibited significantly by streptovaricin, a known inhibitor of RNA primer formation. A selective enrichment in the level of this subcomplex was obtained by manipulating a thymine-requiring mutant. The synthetic capabilities of an enriched and nonenriched DNA-membrane complex were compared in the presence and absence of streptovaricin. Although the rate and extent of DNA synthesis per unit of protein were approximately the same in the absence of the antibiotic, there was a much greater inhibition of synthesis shown by the enriched complex in the presence of streptovaricin. Although the amount of DNA present in the putative initiation subcomplex was less than 0.3 to 0.4% of the total DNA present in the crude complex, such DNA, except for a few quantitative differences, was still representative of genomic DNA. Newly synthesized DNA hybridized to specific origin- and non-origin-derived restriction fragments of the B. subtilis genome. However, when an elongation inhibitor (ddCTP) was added, hybridization of such DNA to almost all of the nonorigin fragments disappeared or was reduced drastically, whereas origin region hybridization patterns remained strong. The highest level of hybridization in the origin region occurred with a BamHI (B7) restriction fragment of 5.6 kilobases that has been implicated by others as one site initiation in vivo (N. Ogasawara, M. Seiki, and H. Yoshikawa, Nature (London) 281:702-704, 1979; S. J. Seror-Laurent and G. Henckes, Proc. Natl. Acad. Sci. USA 82:3586-3590, 1985).